2004
DOI: 10.1007/s10751-005-9013-7
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the EFG Values Measured at the Cd Impurity in a Group of Cu-based Delafossites and the Semiconducting Properties of the Latter

Abstract: In this paper we analyze trend of EFG values measured at Cd impurity in a group of semiconducting delafossites with chemical formula CuBO 2 (B = Al, Fe, Cr, Nd). We conclude that this trend reveals one of the most subtle details in electronic spectrum of the compounds: if impurity states are formed within or out of the band gap. In CuAlO 2 and CuFeO 2 the Cd EFG exhibits larger value than in CuCrO 2 and CuNdO 2 , when Cd substitutes the Cu atom. This occurs because in the first two compounds the Cd forms shall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Several groups theoretically calculated the effects on the electronic behavior of the material due to the presence of various cations in Cu and/or Al sites. Lalić et al [188][189][190] showed that Cd and Zn substitutions on Cu site would produce n-type conductivity in the material, whereas Ni doping in Cu sites would enhance the p-type conductivity of the material. But Cd doping on Al sites would have no effect on the electrical properties of the material.…”
Section: In This Conformation Eight Electrons (Including 2smentioning
confidence: 99%
“…Several groups theoretically calculated the effects on the electronic behavior of the material due to the presence of various cations in Cu and/or Al sites. Lalić et al [188][189][190] showed that Cd and Zn substitutions on Cu site would produce n-type conductivity in the material, whereas Ni doping in Cu sites would enhance the p-type conductivity of the material. But Cd doping on Al sites would have no effect on the electrical properties of the material.…”
Section: In This Conformation Eight Electrons (Including 2smentioning
confidence: 99%